Penerapan Teknologi Digital dalam Memberikan Intervensi pada Pasien dengan Diabetes Mellitus - Devangga Darma Karingga; Ferry Efendi; Retno Indarwati; Punomo Punomo; Evi Tunjung Fitriani (Jurnal Keperawatan Silampari, 2022)
This study aims to look at the effectiveness of digital interventions or the results of a combination of mhealth, which produce innovations in implementing interventions for people with diabetes mellitus. This research method uses a systematic review by searching the literature through 5 databases, ProQuest, Scopus, ScienceDirect, CINAHL, and SAGE which are limited to the last five years. The results of the study show that of the eight articles found, it is stated that the use of digital media is very effective in providing practical interventions and increasing personal knowledge, which has an impact on improving quality of life (QOL). In conclusion, using SMS technology, web, telephone, and mobile applications effectively provides interventions for people with diabetes mellitus to improve their quality of life. Keywords: Diabetes Mellitus, Mobile Health, Mobile App, Mobile Clinics, mHealth